PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER BERBANTUAN HANDOUT TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI IPA SMAN 7 PADANG - Rahmad Wasi Siregar (PILLAR OF PHYSICS EDUCATION, 2013)
Researh to improve student centered learning need tobe done. The objective of this research was to improve interaction, communication, and cooperation of students in NHT type Cooperative Learning Model by using handout learning material that can increase learning result of students. This research can be categorized into “quasi-experimental research” uses “randomized control group only design”. The population of this research was all student in grade XI science  SMAN 7 Padang that enrolled in the academic year 2012/2013. The research samples were determined through two phases that is purposive sampling(first phase) and cluster sampling(second phase), grades choice as research samples were XI IPA 5 and XI IPA 6. Instruments to collect the data were observation sheet and test of learning result. In this research, there were two techniques, those are: percentage technique and two-mean correlation analysis. Base on the data analysis can be state that the result of this research was application NHT type cooperative learning model uses handout learning material can improve learning result of students for cognitive and affective field.   Keywords: Cooperative Learning Model, Handout, Learning Result, NHT.